Strain relaxation in GaN films as a function of growth direction and buffer layer measured by Raman spectroscopy - Seitz, R.
We studied the residual strain in hexagonal GaN epitaxial layers grown exactly or slightly off the (0001) direction on sapphire substrates with either GaN or AlN buffer layers (BLs). The residual strain was determined by Raman spectroscopy. The results were compared with photoluminescence (PL) measurements. We found that the samples with an AlN buffer layer show a residual compressive strain which depends on the misorientation between substrate and growth direction. The residual compressive strain decreases with increasing misorientation. A good correlation exists between Raman and PL measurements. Samples with GaN BL instead show a residual tensile strain which also depends slightly on the misorientation. The correlation between misorientation and residual strain can in this case only be established by Raman measurements.